Experimental Analysis on Dynamic Response of X-Section Piled Raft Composite Foundation under Cyclic Axial Load for Ballastless Track in Soft Soil - Qiang Fu (Shock and Vibration)
Large-scale model tests were established at a scale of 1/5 using a 7 m deep model tank with cross-sectional dimension of 5 m × 4 m, to study the vibration response characteristics of ballastless track, embankment, and X-section piled raft foundation under cyclic axial load, including the vibration displacement, velocity, dynamic soil, and pile stress. Cyclic dynamic loading can be achieved by controlling the loading frequency and cycles through the vibration servo control loading system. The test results are presented in the variation of dynamic displacement, velocity, and stress of X-section piled raft composite foundation. The vibration displacement, velocity, and stress of the track, embankment, and pile foundation follow a pattern of vibration characteristics of loading sine wave. The vibration characteristics of loading waves can be identified easily from the peaks and troughs in the dynamic response of displacement, velocity, and stress at many locations of track slab, embankment, cushion, and underlying soil, at which the vibration response presents almost monotonically increasing tendency with the loading frequencies. With the increase of loading frequency, the vibration responses at the track structure and embankment have higher increasing rates than those at substructure (raft, cushion, and subsoil). The piled raft bears more dynamic load than cushion and subsoils, to ensure long-term dynamic stability and safety of the foundation soils. The model testing results provide a better understanding of the dynamic response characteristics of ballastless track, embankment, and X-section piled raft foundation under cyclic axial load in soft soil.